Determinants and Impact of Foreign Institutional Investors: An Indian Perspective - Jain, Puneet (2007)
Growth of Indian economy is a bit shy of 9% mark. The latter is a rough guide which the foreign investors reckon with, before committing large sums of money for investment. India is one of the biggest and fastest growing developing economies and has attracted the most investor attention in recent years. After liberalization of the Indian economy in 1991, it has become one of the hotspots for global investment. Foreign investment (both Foreign Direct Investment and Foreign Institutional Investment) helped to boost India's economic growth and transformed several sectors of the Indian Industry into globally competitive entities India is also the world's second fastest growing economy and boasts of highly competitive private companies, a booming stock market, and a modern, well-disciplined financial sector. The Indian stock markets witnessed unprecedented buoyancy during 2006-07 (Dalal Street, 2006).